2022
DOI: 10.3390/plants11223182
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Beauveria bassiana Induces Oxidative Stress and Enhances the Growth of Fusarium oxysporum-Infected Tomato Plants

Abstract: Studying the mechanisms through which endophytic fungi confer protection to host plants against parasites will contribute toward elucidating the endophytic fungi–plant–pathogen relationship. In this study, we evaluated the effects of endophytic Beauveria bassiana on the antioxidant activity, oxidative stress, and growth of tomatoes infected with the fusarium wilt pathogen, Fusarium oxysporum f. sp. lycopersici (FOL). Tomato seedlings were inoculated with B. bassiana conidia and then contaminated with FOL exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The high activity of the antioxidant system and consequent downregulation of MDA indicate the absence of a pathological imbalance within the system of stress-induced protective mechanisms. An increase in the activity of antioxidant enzymes has been documented in most papers on the adaptogenic properties of endophytic fungi in relation to plants grown under salinity stress [60,[62][63][64]67,68] and after the application of B. bassiana [46,47,92]. In our experiments, there were no significant changes in the MDA concentration of the roots, regardless of the presence or absence of salt and/or the endophyte.…”
Section: Discussionsupporting
confidence: 62%
“…The high activity of the antioxidant system and consequent downregulation of MDA indicate the absence of a pathological imbalance within the system of stress-induced protective mechanisms. An increase in the activity of antioxidant enzymes has been documented in most papers on the adaptogenic properties of endophytic fungi in relation to plants grown under salinity stress [60,[62][63][64]67,68] and after the application of B. bassiana [46,47,92]. In our experiments, there were no significant changes in the MDA concentration of the roots, regardless of the presence or absence of salt and/or the endophyte.…”
Section: Discussionsupporting
confidence: 62%
“…37,38 In the last decades, it has been demonstrated that Beauveria bassiana can be artificially introduced into tomato using different inoculation methods such as leaf spraying, root irrigation, stem injection, and seed treatments. 21,28,39,40 These methods can influence the colonization efficiency of Beauveria bassiana within the tomato tissues. In our early research, we found that colonization efficiency reached 100% in 14 days when tomatoes were inoculated with Beauveria bassiana Bb252 by leaf spraying.…”
Section: Discussionmentioning
confidence: 99%
“…Endophytic EPF of plants inhabit plant tissues over a long period and provide many benefits to plants, such as reducing the influence of abiotic factors on the control effect of EPF 37,38 . In the last decades, it has been demonstrated that Beauveria bassiana can be artificially introduced into tomato using different inoculation methods such as leaf spraying, root irrigation, stem injection, and seed treatments 21,28,39,40 . These methods can influence the colonization efficiency of Beauveria bassiana within the tomato tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Nchu et al [15] deepened the relationship between the endophyte fungus and the plant pathogen. They studied the effects of Beauveria bassiana on the growth of tomato plants infected with Fusarium oxysporum f. sp.…”
Section: Special Issue Contentsmentioning
confidence: 99%